JPG تقنيتي آلة المتجه الداعم ومميز فيشر الخطي للكشف عن الإخفاء في - سماح فخري عزيز; أحمد سامي نوري (PROSPECTIVE RESEARCHES, 2023)
Steganography is considered as the new and the complementary system of Cryptography that took a long time in transferring secret and important messages through the networks and the Internet. Then there was the emergence of what complements Steganography as a science that analysis and discover the content of the secret messages and this science is (Steganalysis). For Steganalysis in colored images, the work relied on two important technologies; the first is called Support Vector Machine (SVM) and the second is called Fisher Linear Discriminator (FLD). The SVM technology has been used with the (blind) application idea while FLD has been used with the (blind and non-blind) application ideas using best type of colored images JPG. Results proved the high efficiency of the two technologies in detecting the image that includes the secret messages and comparisons were varied between the two technologies in terms of detection rate, fault and the execution time.